Peutz-Jeghers Type Polyp of the Appendix with Review of Literature - Jolanta Jedrzkiewicz; Keith Quencer; Anna P. Matynia; Ellen Morrow; Maria Pletneva; Gonzalo Barraza (Case Reports in Pathology, 2019)
Hamartomatous polyps of Peutz-Jeghers type are strongly associated with Peutz-Jeghers polyposis syndrome and are predominantly encountered in the small intestine. Sporadic cases are uncommonly reported. We report a case of a polyp identified incidentally in the appendix of a patient undergoing diagnostic imaging due to a history of hepatitis C infection. Histopathologic evaluation after appendectomy showed a polyp with bands of muscularis mucosae bundles with arborizing architecture and variable amounts of inspissated mucin, morphologically indistinguishable from Peutz-Jeghers type hamartomatous polyp. A family or personal history of abdominal cancers was not reported by the patient, suggesting a sporadic occurrence. Next generation sequencing revealed only two pathogenic low-level STK11 mutations, presumed to be somatic. In conclusion, this is an unusual case of a sporadic Peutz-Jeghers type polyp occurring in the appendix.